Electrochemical hydrogen storage characteristics of Mg2-xCxNi (x = 0, 0.1, 0.2, 0.5) alloys prepared by mechanical alloying - Haghanifar, S. (Asian Research Publishing Network, 2016)
Mg2-xCxNi (x = 0, 0.1, 0.2, 0.5) type alloys were prepared by mechanical alloying and their electrochemical hydrogen storage characteristics were investigated in 6 M KOH solution. Characterization of the crystal structure of the milled products using X-ray diffractometry exhibited the formation of Mg2Ni-based nano-crystallites after ~5h for the initial mixture with stoichiometric composition of Mg2Ni and Mg1.9C0.1Ni. However, Mg2Ni-based nano-crystallites were synthesized after 15 and 20h of milling in the case of Mg1.8C0.2Ni and Mg1.5C0.5Ni, respectively. The results show that increasing the carbon content of initial powder mixture decreases the formation kinetics of Mg2Ni-based nano-crystallites. In addition, increasing milling time resulted in decreasing and increasing the mean crystallite size and lattice strain of Mg2Ni structure in all milled products. Furthermore, the negative electrode made from Mg1.9C0.1Ni ternary milled product after 30 hour of milling exhibited the highest initial discharge capacity and longest discharge life at all the ball milling durations. This observation was attributed to the formation of the porous unstable Mg(OH)2 layer due to the intercalation of Mg, which have the high rate of solubility in strongly basic solutions, and thus the exposition of the underlying electro catalytically active Ni sites for the sample without carbon addition. Â© 2006-2016 Asian Research Publishing Network (ARPN).